On Schrödinger-Poisson equations with a critical nonlocal term - Xinyi Zhang; Jian Zhang (AIMS Mathematics, 2024)
In this paper, we study the following non-autonomous Schrödinger-Poisson equation with a critical nonlocal term and a critical nonlinearity: